Leveraging Biodiversity Action From Plural Values: Transformations of Governance Systems - Leventon, Julia; Duşe, Ioana A.; Horcea-Milcu, Andra-Ioana (Frontiers in Ecology and Evolution, 2021)
In this paper, we argue that leveraging plural values into action for biodiversity requires a focus on transforming the biodiversity governance system. We draw on Donella Meadows’ concept of Leverage Points, which outlines the “depth” of intervention in order to shift a system toward sustainability. Engaging with deep leverage points (system intent and goals) is argued to lead to greater transformation than engaging with shallow leverage points (system design and materials). We outline how embracing plural values of biodiversity requires changes at deeper systems properties within governance systems to create space to reflect diversity in values and knowledge systems, and move away from a focus on commodification of nature’s contributions to people. We point toward political and policy sciences to highlight frameworks and concepts for understanding governance system transformation. We conclude with a call for meaningful engagement with such sciences in ongoing research.